Students with Attention Deficit Hyperactivity Disorder Participating in Recess - Lucas, Matthew D.; Justice, Michael J.; Rosko, Kelly M. (Journal of the American Academy of Special Education Professionals, 2014)
The participation of a student with Attention Deficit Hyperactivity Disorder (ADHD) in recess can often be both challenging and rewarding for the student and teacher. This paper will address common characteristics of children with ADHD and present basic solutions to improve the experience of these children in the recess setting. Initially, the definition, symptoms, and prevalence of ADHD will be presented. The paper will then address benefits of recess, followed by recommendations for children with ADHD participating in recess. Lastly, the paper will describe a common activity played at recess, and possible modifications to the activity for children with ADHD.